2019
DOI: 10.1155/2019/9821535
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Morphological Control, and Antibacterial Performance of Ag/TiO2 Micro-Nanocomposite Materials

Abstract: Structures, morphological control, and antibacterial activity of silver-titanium dioxide (Ag/TiO2) micro-nanocomposite materials against Staphylococcus aureus are investigated in this study. Horizontal vapor phase growth (HVPG) technique was used to synthesize the Ag/TiO2 micro-nanomaterials, with parameters of growth temperature and baking time. The materials were characterized by using scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, and atomic force microscope (AFM). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The Ag/TiO 2 photocatalysts are efficient to act as biocides to kill bacteria belonging to both Gram-positive (Gram+) and Gram-negative (Gram-) groups such as Escherichia coli (Liu et al 2012), Staphylococcus aureus (Zawadzka et al 2016), Klebsiella pneumonia (Ryu et al 2015), Staphylococcus epidermidis (Ramesh et al 2012), Pseudomonas aeruginosa (Gupta et al 2013), Bacillus subtilis (Khan et al 2013), Penicillium expansum (Yaithongkum et al 2011), and many others. Size, shape, and silver concentration are the major factors influencing the antibacterial activity of silver-doped TiO 2 nanocomposites and determining their interaction behavior with cells (Yu et al 2011;Bahadur et al 2016;Muflikhun et al 2019). Ag/ TiO 2 photocatalysts, with smaller particle sizes (with diameters below 10 nm) exhibit effective higher bactericidal activity against bacterial species than those with bigger sizes (Frommelt et al 2019;Dung et al 2020).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The Ag/TiO 2 photocatalysts are efficient to act as biocides to kill bacteria belonging to both Gram-positive (Gram+) and Gram-negative (Gram-) groups such as Escherichia coli (Liu et al 2012), Staphylococcus aureus (Zawadzka et al 2016), Klebsiella pneumonia (Ryu et al 2015), Staphylococcus epidermidis (Ramesh et al 2012), Pseudomonas aeruginosa (Gupta et al 2013), Bacillus subtilis (Khan et al 2013), Penicillium expansum (Yaithongkum et al 2011), and many others. Size, shape, and silver concentration are the major factors influencing the antibacterial activity of silver-doped TiO 2 nanocomposites and determining their interaction behavior with cells (Yu et al 2011;Bahadur et al 2016;Muflikhun et al 2019). Ag/ TiO 2 photocatalysts, with smaller particle sizes (with diameters below 10 nm) exhibit effective higher bactericidal activity against bacterial species than those with bigger sizes (Frommelt et al 2019;Dung et al 2020).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The results show that by changing curing time and growth temperature, different nanomaterials were produced with different shapes, such as Nanoparticles, Nanorods, Triangular Nanomaterials, and Cotton-like Nanomaterials. The results were then evaluated using SEM-EDX to determine the best shape for different applications such as for anti-bacterial [1,21] and elemental composition. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ubonchonlakate et al [17] and Muflikhun et al [18] described the formation of noticeable growth "inhibition zones" for various strains of bacteria around substrates impregnated with TiO 2 /Ag sols (owing to the combination of the photocatalytic properties of TiO 2 and the plasmon resonance effect on Ag). Tryba et al [19] described the use of nano-TiO 2 /Ag on fabric supports as a disinfectant, and Rodriguez et al [20] reported the application of TiO 2 /Ag in self-cleaning coatings.…”
Section: Theoretical Analysismentioning
confidence: 99%